2018
DOI: 10.1590/2317-1545v40n4207216
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of primed tobacco seeds

Abstract: Priming is a commercial technique used to increase the speed and uniformity of seed germination. However, the physiological quality of primed seeds is usually negatively affected during storage. Tobacco seeds of the cultivar BAT 2101 were used to investigate whether primed seeds could be cryopreserved. The most suitable substances, type of drying, and reheating during priming and cryopreservation of tobacco seeds were studied. Seed priming was performed with water, spermidine, and potassium nitrate, and drying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
6
1
Order By: Relevance
“…Seeds were harvested on plants before pod shattering and removed from fruits, after that, were stored in cold chamber for about 20 days, when the experiments were started. Priming consisted in five solutions: distilled water, 0.2% potassium nitrate (Cardoso et al, 2015), 0.5 mmol.L -1 spermidine (SPE) (Hussain et al, 2015;Lopes et al, 2018), 50 mg.L -1 gibberellin (GA) (Batista et al, 2015;Cardoso et al, 2015), and 0.10 mmol.L -1 sodium nitroprusside (SNP) (Faraji and Sepehri, 2018). Treatments consisted in immersion of 40 g seeds in 400 mL of above-described solutions in Erlenmeyer, being the solution kept aerated with the support of an air compressor.…”
Section: Methodsmentioning
confidence: 99%
“…Seeds were harvested on plants before pod shattering and removed from fruits, after that, were stored in cold chamber for about 20 days, when the experiments were started. Priming consisted in five solutions: distilled water, 0.2% potassium nitrate (Cardoso et al, 2015), 0.5 mmol.L -1 spermidine (SPE) (Hussain et al, 2015;Lopes et al, 2018), 50 mg.L -1 gibberellin (GA) (Batista et al, 2015;Cardoso et al, 2015), and 0.10 mmol.L -1 sodium nitroprusside (SNP) (Faraji and Sepehri, 2018). Treatments consisted in immersion of 40 g seeds in 400 mL of above-described solutions in Erlenmeyer, being the solution kept aerated with the support of an air compressor.…”
Section: Methodsmentioning
confidence: 99%
“…Each treatment was primed in a single Erlenmeyer flask, without replications. The priming solutions used were distilled water (water), 0.2% potassium nitrate solution (KNO 3 ) (Cardoso et al, 2014;Cardoso et al, 2015), 0.5 mmol.L −1 spermidine solution (SPER) (Hussain et al, 2015;Lopes et al, 2018), 50 mg.L −1 pure gibberellin solution (GB) (Batista et al, 2015;Cardoso et al, 2015), and 0.10 mmol.L −1 sodium nitroprusside solution (SNP) (Ataíde et al, 2015;Silva et al, 2015;Faraji et al, 2018). The seeds used as a control were not primed.…”
Section: Methodsmentioning
confidence: 99%
“…Various authors have found that the positive effects of the SPER are associated with maintenance of membrane integrity, regulation of gene expression, breaking of dormancy, and seed germination, flower and fruit development, and senescence (Gupta et al, 2014;Lopes et al, 2018;Yalamalle et al, 2019). In addition, the SPER also plays a crucial role in tolerance to abiotic stresses (Yalamalle et al, 2019).…”
Section: Journal Of Seedmentioning
confidence: 99%
“…Therefore, it also has the potential to be applied to forage grass seeds, helping to increase the speed and uniformity of seed germination with positive impacts on pasture formation (Batista et al, 2016). Osmopriming can be performed using different osmotic solutions, such as spermidine (Lopes et al, 2018), gibberellin (Li et al, 2019), sodium nitroprusside (SNP) (Kaiser et al, 2016), polyethylene glycol (PEG-6000) (Lei et al, 2021), and sodium selenate (Silveira et al, 2023). Oliveira et al (2021) evaluated the effect of osmopriming with SNP in U. brizantha seeds and found an improvement in the physiological performance of seeds under water and saline stress conditions.…”
Section: Introductionmentioning
confidence: 99%